ANALYSIS OF THE EFFECT OF FINANCING ON PROFITABILITY IN SHARIA COMMERCIAL BANKS - Lustiana, Fifi Ulfa; Nurhayati, Immas; Suharti, Titing (Manager : Jurnal Ilmu Manajemen, 2023)
This study aims to determine the effect of the composition of financing on the profitability of banks in Indonesia by using the Ratio of Return on Assets (ROA). The analytical tool used is simple regression analysis. This type of research method is quantitative descriptive research. The type of data used in this study is secondary data, four sample BUS were selected as samples including, Bank Muamalat Indonesia Syariah, Bank BJB Syariah, Bank BCA Syariah, Bank Bukopin Syariah, financing used as a variable including profit sharing, murabahah, qord, and ijarah. The results showed that the profit sharing variable had a significant positive effect on ROA, murabahah had a significant negative effect on ROA, qord had a significant positive effect on ROA, and ijarah had a significant positive effect on ROA.